Odpowiedź:
[tex]x=\frac{39}{16}[/tex]
Szczegółowe wyjaśnienie:
[tex]1+(2x-4)+(2x-4)^{2}+...=8[/tex]
Stąd wynika od razu, że:
[tex]a_{1}=1\\q=2x-4[/tex]
Aby równanie miało sens, to szereg musi być zbieżny. Będzie tak, gdy [tex]|q|<1[/tex], więc:
[tex]|2x-4|<1\\|x-2|<\frac{1}{2} \\x-2<\frac{1}{2} \wedge x-2>-\frac{1}{2}\\x<\frac{5}{2} \wedge x>\frac{3}{2} \\x \in (\frac{3}{2},\frac{5}{2})[/tex]
Obliczamy sumę:
[tex]S=\frac{1}{1-2x+4} =\frac{1}{5-2x}[/tex]
Zatem równanie ma postać:
[tex]\frac{1}{5-2x}=8\\1=8(5-2x)\\1=40-16x\\-16x=-39\\x=\frac{39}{16} \in (\frac{3}{2},\frac{5}{2})[/tex]